The macroeconomic repercussions of agricultural shocks and their implications for insurance - Paul Collier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The paper considers the macroeconomic impact of shocks to agricultural output and of negative and positive price shocks. It is shown that negative price shocks have particularly large externalities: it is estimated that the overall impact of these negative shocks on GDP may well be double their direct impact. In terms of policy, the presence of externalities justifies subsidising the provision of insurance. If insurance is not feasible, then foreign aid may be helpful. Turning to other systemic shocks, it is argued that the macroeconomic consequences of negative output shocks are far less important. Positive price shocks also have substantial macroeconomic externalities via their effect on asset demand. Appropriate central bank policy is crucial and requires a detailed understanding of asset demand changes in response to price shocks. Since this may well be unlikely, dollarization may be a better strategy. – agriculture ; price shocks ; insurance ; price stabilization ; dollarization
Keywords: O13; E30; E58; Q17; 330; Landwirtschaft; Schock